Preparation method and application of active coating liquid loaded with pepper essential oil

By using the zein-citrus pectin composite nanoparticle carrier, pepper essential oil was combined with it to prepare an active coating solution loaded with pepper essential oil, which solved the problem of poor uniform distribution of pepper essential oil in a hydrophilic environment, and achieved effective preservation of pepper and extended shelf life.

CN119899557AActive Publication Date: 2025-04-29NORTHWEST A & F UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510086639.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The uniform distribution effect of pepper essential oil in a hydrophilic environment is poor, which limits its application in food preservation.

Method used

The zein-citrus pectin composite nanoparticles were used as the carrier, and the pepper essential oil was combined with the composite nanoparticles by electrostatic adsorption method to prepare an active coating liquid loaded with pepper essential oil.

Benefits of technology

It improves the stability and uniform distribution effect of pepper essential oil in a hydrophilic environment, delays the aging of peppers, improves the freshness effect, and extends the shelf life of peppers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250311670000091
    Figure BDA0005250311670000091
  • Figure BDA0005250311670000111
    Figure BDA0005250311670000111
  • Figure BDA0005250311670000112
    Figure BDA0005250311670000112
Patent Text Reader

Abstract

The invention provides a preparation method and application of active coating liquid loaded with pepper essential oil, and relates to the technical field of fruit and vegetable preservation. A preparation method of the active coating liquid loaded with the Chinese prickly ash essential oil comprises the following steps: preparing 3.5% zein nanoparticles; preparing a 3.5% citrus pectin solution; dropwise adding 3.5% of zein nanoparticles into the citrus pectin solution to obtain a zein-citrus pectin Pickering emulsion; mixing pepper essential oil with 3.5% zein-citrus pectin Pickering emulsion to obtain pepper essential oil-loaded Pickering emulsion; sodium carboxymethyl cellulose is taken and dissolved in deionized water; adding glycerol; adding the pepper essential oil loaded Pickering emulsion at room temperature, standing and defoaming to obtain the pepper essential oil loaded active coating liquid. The method is beneficial to inhibiting putrefying flora of the fresh red peppers, delaying the aging time of the peppers and prolonging the fresh-keeping period of the peppers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fruit and vegetable preservation, and in particular to a preparation method of an active coating liquid loaded with zanthoxylum essential oil and application thereof. Background Art

[0002] Zanthoxylum bungeanum essential oil (ZBEO), also known as Zanthoxylum bungeanum essential oil, is an oily mixture extracted from the peel of Zanthoxylum bungeanum. It has a strong aroma, strong volatility, and is mostly yellow. ZBEO has many functional activities, such as broad-spectrum antibacterial, antioxidant, anesthetic analgesic, insecticide, etc., and is often used in food processing, cosmetics development, pharmaceutical production and other fields. However, the poor stability and poor hydrophilicity of ZBEO also weaken its functional activity if it is directly added to the preservation system in actual application, and also greatly limits its scope of application. Therefore, how to improve the application shortcomings of ZBEO, enhance its uniform distribution effect in a hydrophilic environment, and broaden its application scenarios are the current focus of ZBEO application research. In this case, various hydrophilic encapsulation methods have gradually been used to improve the application shortcomings of ZBEO. Pickering emulsion is one of the widely used hydrophilic encapsulation methods. The advantages of food-grade Pickering solid particles, which are natural, green and biodegradable, also provide greater application safety advantages for the prepared emulsion. Zein is abundant in resources and low in cost. Its nanoparticles (Zeinnanoparticles, ZNPS) can be prepared by anti-solvent precipitation method and are often used in the preparation of Pickering emulsions. However, ZNPS itself is too hydrophobic and easily aggregates and precipitates in solution, and its emulsion cannot be stable for a long time. Therefore, in practical applications, it is usually not used alone, but it is compounded with other biomacromolecules to prepare nanoparticles, which are then used in the preparation of Pickering emulsions, which not only significantly improves the stability of the emulsion, but also expands its functional properties. Citrus pectin (Citrus Pectin, CP) is a negatively charged biopolysaccharide, while Zein is positively charged, so the two can be combined into composite nanoparticles through electrostatic adsorption and hydrophobic interaction to improve the hydrophilicity of Zein. In recent years, many studies on the use of pectin from different sources and ZNPS to stabilize Pickering emulsions have demonstrated the ability of Zein-Citrus pectin composite nanoparticles (ZCPS) to stabilize Pickering emulsions and its huge development potential. The coating preservation technology refers to a food preservation technology that uses natural and degradable biomacromolecules as the main component to prepare a coating liquid, which is solidified on the surface of food by brushing, dipping, spraying or self-assembly to form a dense film, isolating the food from the external environment and inhibiting the growth and reproduction of microorganisms, thus protecting the food. The film formed by the coating preservation technology not only serves as food packaging, but also as a carrier of biologically active ingredients such as nutrients, antioxidants, and antibacterial agents, thereby improving food quality and extending shelf life. Summary of the invention

[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a method for preparing an active coating liquid loaded with Zanthoxylum essential oil and its application in the preservation of peppers. By preparing an active coating liquid loaded with Zanthoxylum essential oil, soaking the peppers in the coating liquid and then taking them out to air-dry, the aging of the peppers can be delayed, the preservation effect can be improved, and the storage quality of the peppers can be maintained.

[0004] Technical solution: A method for preparing an active coating liquid loaded with Zanthoxylum bungeanum essential oil, comprising the following steps: S1: Zein was completely dissolved in 85% ethanol, and the precipitate was removed by centrifugation to obtain a supernatant; the supernatant was added dropwise to distilled water under magnetic stirring, and concentrated by a rotary evaporator after ultrasonic treatment to obtain 3.5% zein nanoparticles; S2: Add citrus pectin to distilled water and stir overnight at 25°C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution under magnetic stirring to obtain zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed, and treated with a high-speed disperser at 14000 rpm for 4 min to obtain a Zanthoxylum bungeanum essential oil-loaded Pickering emulsion; S5: Take sodium carboxymethyl cellulose, add deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add glycerol and continue stirring for 1 hour; S6: Add 30-50% Pickering emulsion loaded with Zanthoxylum bungeanum essential oil at room temperature, stir magnetically at a speed of 800 rpm for 1 hour, and let stand to degas, so as to obtain an active coating liquid loaded with Zanthoxylum bungeanum essential oil. Furthermore, in step S1, the centrifugal speed is 5000 g and the centrifugal time is 10 min. Furthermore, in step S1, the ultrasonic power is 600 W and the time is 10 min. Furthermore, in step S3, the volume ratio of 3.5% zein nanoparticles to 3.5% citrus pectin solution is 1:(2-4). Furthermore, in step S4, the volume ratio of Zanthoxylum bungeanum essential oil to 3.5% zein-citrus pectin Pickering emulsion is 1:(8-10). Furthermore, in step S5, the mass volume ratio of sodium carboxymethyl cellulose / deionized water and glycerol is 6g:400mL:3g. Application of the ZCZPE / CMC composite coating liquid prepared by any of the preparation methods described above in the preservation of fresh red peppers. Beneficial effects: 1. The ZCZPE / CMC composite coating liquid prepared by the present invention has a stable system and good antibacterial effect. When applied to pepper preservation, it can reduce the quality loss of fresh red peppers during storage, inhibit the growth of spoilage bacteria, delay the aging of peppers after harvest, maintain the appearance hardness of peppers, extend the shelf life of peppers, and improve storage resistance. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The physicochemical properties of the ZCZPE / CMC composite coating liquid prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Figure A, wherein Figure A is the pH value of the ZCZPE / CMC composite coating liquid; Figure B is the particle size diagram of the ZCZPE / CMC composite coating liquid; Figure C is the ζ-potential diagram of the ZCZPE / CMC composite coating liquid; different letters (ac) in the figure indicate significant differences between different treatment groups (p<0.05); Figure 2 The retention rate of Zanthoxylum bungeanum essential oil in the ZCZPE / CMC composite coating solution prepared in Examples 1-3 and Comparative Examples 1-2; different letters (AE) in the figure indicate significant differences between different treatment groups (p<0.05); Figure 3 The rheological properties of the ZCZPE / CMC composite coating liquid prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Figure A, wherein Figure A is a graph of the apparent viscosity of the ZCZPE / CMC composite coating liquid; Figure B is a graph of the loss tangent of the ZCZPE / CMC composite coating liquid; Figure C is a graph of the storage modulus of the ZCZPE / CMC composite coating liquid; and Figure D is a graph of the loss modulus of the ZCZPE / CMC composite coating liquid; Figure 4 DPPH· and ABTS of the ZCZPE / CMC composite coating solution prepared in Examples 1-3 and Comparative Examples 1-2 + Clearance rate; Different letters (ad, AE) in the figure indicate significant differences among different treatment groups (p<0.05); Figure 5The graphs are the antibacterial rate graphs of the ZCZPE / CMC composite coating liquids prepared in Examples 1-3 and Comparative Examples 1-2, wherein Graph A is the inhibition rate of the CZPE / CMC composite coating liquid on Escherichia coli; Graph B is the inhibition rate of the CZPE / CMC composite coating liquid on Staphylococcus aureus; different letters (ae) in the graph indicate significant differences between different treatment groups (p<0.05); Figure 6 This is a graph showing the weight loss rate of fresh red peppers after being preserved in different ways during storage; Figure 7 This is a graph showing the changes in the decay index of fresh red peppers after they were preserved in different ways during storage; Figure 8 This is a diagram showing the changes in the appearance of fresh red peppers after they are preserved in different ways during storage; Fig. 9 The graphs are color change graphs of fresh red peppers after being preserved in different ways during storage, wherein, Graph A is a L* value change graph of fresh red peppers after being preserved in different ways during storage; Graph B is a* value of fresh red peppers after being preserved in different ways during storage; Graph C is b* value of fresh red peppers after being preserved in different ways during storage; Graph D is ΔE value of fresh red peppers after being preserved in different ways during storage; Fig.10 This is a graph showing the changes in hardness of fresh red peppers after being preserved in different ways during storage; Fig.11 This is a graph showing the changes in soluble solids content of fresh red peppers after being preserved in different ways during storage; Fig.12 This is a graph showing the changes in the malondialdehyde content of fresh red peppers after being preserved in different ways during storage; Fig.13 This is a graph showing the changes in polyphenol oxidase activity of fresh red peppers after they were preserved in different ways during storage; Fig.14 This is a graph showing the changes in peroxidase activity of fresh red peppers after being preserved in different ways during storage. DETAILED DESCRIPTION The present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are explanations of the present invention and the present invention is not limited to the following embodiments: Example 1 A method for preparing a ZCZPE / CMC composite coating liquid comprises the following steps: S1: 1.75 g of zein was completely dissolved in 40 mL of 85% ethanol, and the supernatant was removed by centrifugation at 5000 g for 10 min to obtain a supernatant; the supernatant was added dropwise to 120 mL of distilled water under magnetic stirring, and then concentrated to 50 mL using a rotary evaporator after ultrasonic treatment at 600 W for 10 min to obtain 3.5% zein nanoparticles; S2: 3.5 g of citrus pectin was added to 100 mL of distilled water and stirred overnight at 25 °C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution at a volume ratio of 1:3 under magnetic stirring to obtain a 3.5% zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed in a volume ratio of 1:9 and treated with a high-speed disperser at 14000 rpm for 4 min to obtain ZCZPE; S5: Take 1.5g CMC, add 100mL deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add 0.75g glycerol and continue stirring for 1h; S6: Add 30% ZCZPE at room temperature, stir magnetically at 800 rpm for 1 hour, and let stand to degas, to obtain ZCZPE / CMC composite coating solution. Example 2 A method for preparing a ZCZPE / CMC composite coating liquid comprises the following steps: S1: 1.75 g of zein was completely dissolved in 40 mL of 85% ethanol, and the supernatant was removed by centrifugation at 5000 g for 10 min to obtain a supernatant; the supernatant was added dropwise to 120 mL of distilled water under magnetic stirring, and then concentrated to 50 mL using a rotary evaporator after ultrasonic treatment at 600 W for 10 min to obtain 3.5% zein nanoparticles; S2: 3.5 g of citrus pectin was added to 100 mL of distilled water and stirred overnight at 25 °C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution at a volume ratio of 1:3 under magnetic stirring to obtain zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed in a volume ratio of 1:9 and treated with a high-speed disperser at 14000 rpm for 4 min to obtain ZCZPE; S5: Take 1.5g CMC, add 100mL deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add 0.75g glycerol and continue stirring for 1h; S6: Add 40% ZCZPE at room temperature, stir magnetically at 800 rpm for 1 hour, and let stand to degas, to obtain ZCZPE / CMC composite coating solution. Example 3 A method for preparing a ZCZPE / CMC composite coating liquid comprises the following steps: S1: 1.75 g of zein was completely dissolved in 40 mL of 85% ethanol, and the supernatant was removed by centrifugation at 5000 g for 10 min to obtain a supernatant; the supernatant was added dropwise to 120 mL of distilled water under magnetic stirring, and then concentrated to 50 mL using a rotary evaporator after ultrasonic treatment at 600 W for 10 min to obtain 3.5% zein nanoparticles; S2: 3.5 g of citrus pectin was added to 100 mL of distilled water and stirred overnight at 25 °C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution at a volume ratio of 1:3 under magnetic stirring to obtain zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed in a volume ratio of 1:9 and treated with a high-speed disperser at 14000 rpm for 4 min to obtain ZCZPE; S5: Take 1.5g CMC, add 100mL deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add 0.75g glycerol and continue stirring for 1h; S6: Add 50% ZCZPE at room temperature, stir magnetically at 800 rpm for 1 hour, and let stand to degas, to obtain ZCZPE / CMC composite coating solution. Comparative Example 1 A method for preparing a ZCZPE / CMC composite coating liquid comprises the following steps: S1: 1.75 g of zein was completely dissolved in 40 mL of 85% ethanol, and the supernatant was removed by centrifugation at 5000 g for 10 min to obtain a supernatant; the supernatant was added dropwise to 120 mL of distilled water under magnetic stirring, and then concentrated to 50 mL using a rotary evaporator after ultrasonic treatment at 600 W for 10 min to obtain 3.5% zein nanoparticles; S2: 3.5 g of citrus pectin was added to 100 mL of distilled water and stirred overnight at 25 °C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution at a volume ratio of 1:3 under magnetic stirring to obtain zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed in a volume ratio of 1:9 and treated with a high-speed disperser at 14000 rpm for 4 min to obtain ZCZPE; S5: Take 1.5g CMC, add 100mL deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add 0.75 glycerol and continue stirring for 1h; S6: Add 10% ZCZPE at room temperature, stir magnetically at 800 rpm for 1 hour, and let stand to degas, to obtain ZCZPE / CMC composite coating solution. Comparative Example 2 A method for preparing a ZCZPE / CMC composite coating liquid comprises the following steps: S1: 1.75 g of zein was completely dissolved in 40 mL of 85% ethanol, and the supernatant was removed by centrifugation at 5000 g for 10 min to obtain a supernatant; the supernatant was added dropwise to 120 mL of distilled water under magnetic stirring, and then concentrated to 50 mL using a rotary evaporator after ultrasonic treatment at 600 W for 10 min to obtain 3.5% zein nanoparticles; S2: 3.5 g of citrus pectin was added to 100 mL of distilled water and stirred overnight at 25 °C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution at a volume ratio of 1:3 under magnetic stirring to obtain zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed in a volume ratio of 1:9 and treated with a high-speed disperser at 14000 rpm for 4 min to obtain ZCZPE; S5: Take 1.5g CMC, add 100mL deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add 0.75g glycerol and continue stirring for 1h; S6: Add 20% ZCZPE at room temperature, stir magnetically at 800 rpm for 1 hour, and let stand to degas, to obtain ZCZPE / CMC composite coating solution. Performance Testing (1) Determination of pH value of ZCZPE / CMC composite coating liquid The pH value of the ZCZPE / CMC composite coating solution prepared in the above examples and comparative examples was measured at room temperature, and the pH value was measured three times and the average value was taken as the experimental result. like Figure 1 As shown in (A), as the addition ratio of ZCZPE increases, the pH value of the ZCZPE / CMC composite coating solution decreases. When the addition ratio of ZCZPE reaches 50%, the pH value of the ZCZPE / CMC composite coating solution drops to 4.45. (2) Particle size and ζ-potential determination of ZCZPE / CMC composite coating liquid The ZCZPE / CMC composite coating liquid prepared in the above examples and comparative examples was diluted to different concentrations at room temperature according to the instrument analysis requirements, and the average particle size was measured using a laser particle size analyzer. The pump speed was set to 60%, and 1 min was waited before each measurement. The ζ-potential of the ZCZPE / CMC composite coating liquid prepared in the above examples and comparative examples was measured after the emulsion was diluted to an appropriate concentration (attenuation value = 7) with deionized water. pass Figure 1 (B) It can be found that the particle size of the ZCZPE / CMC composite coating liquid with different ZCZPE addition ratios generally shows a trend of first increasing and then decreasing with the increase of the ZCZPE addition ratio. When the ZCZPE addition ratio is 10%, the pH value of the ZCZPE / CMC composite coating liquid is the highest. At this time, the ZCZPE system is unstable, but the ZCZPE / CMC composite coating liquid shows a smaller particle size. The reason may be that the high concentration of CMC matrix solution plays a stabilizing role in the entire ZCZPE / CMC composite coating liquid system, providing a strong steric hindrance for ZCZPE, limiting the movement of ZCZPE droplets in the ZCZPE / CMC composite coating liquid system, making the particle size of the entire system smaller. As the addition ratio of ZCZPE increases, the proportion of the corresponding CMC matrix solution in the composite coating liquid system decreases, and the steric hindrance effect provided by it decreases. However, the pH value of the ZCZPE / CMC composite coating liquid still has a significant impact on the stability of ZCZPE. Therefore, when the ZCZPE addition concentration rises to 20%, the particle size of the ZCZPE / CMC composite coating liquid system increases sharply. As the addition ratio of ZCZPE continues to increase, the pH value of the ZCZPE / CMC composite coating liquid gradually decreases, which makes the stability of ZCZPE in the ZCZPE / CMC composite coating liquid system continue to improve, and the particle size of the ZCZPE / CMC composite coating liquid gradually decreases. When the addition ratio of ZCZPE increases to 50%, the pH value of the ZCZPE / CMC composite coating liquid reaches the minimum, which is most conducive to the stability of ZCZPE in the ZCZPE / CMC composite coating liquid system. At this addition ratio, the particle size of the ZCZPE / CMC composite coating liquid reaches a minimum of 3.3μm. from Figure 1(C) It can be found that with the increase of the addition ratio of ZCZPE and the decrease of the CMC coating matrix ratio of ZCZPE in the ZCZPE / CMC composite coating liquid system, the absolute value of the ζ-potential of the composite coating liquid continues to decrease, but it is always greater than 30mV. When the absolute value of the system ζ-potential is greater than 30mV, the entire system can be considered to be a stable system. (3) Determination of the retention rate of Zanthoxylum bungeanum essential oil in ZCZPE / CMC composite coating solution First, 10 mL of the ZCZPE / CMC composite coating solution prepared in the above-mentioned embodiments and comparative examples was injected into a disposable plastic culture dish (d=90 mm), and the film was obtained by air drying at room temperature for 12 hours. One piece of each different film was placed in a 100 mL conical flask, 30 mL of n-hexane was added, and a magnetic stirrer was used to vigorously stir overnight at room temperature. The solution was then centrifuged at 11000 rpm for 20 min by a high-speed refrigerated centrifuge, the supernatant was diluted to a suitable concentration, and the absorbance value was measured at 268 nm by an ultraviolet spectrophotometer to calculate the content of pepper essential oil in the film. The pepper essential oil content in the ZCZPE / CMC composite coating solution containing different ZCZPE addition ratios was also determined by an ultraviolet spectrophotometer. The retention rate of pepper essential oil in the ZCZPE / CMC composite coating solution prepared in the above-mentioned embodiments and comparative examples is the ratio of the pepper essential oil content in the film to the pepper essential oil content in the composite coating solution, and each sample was repeated three times. Figure 2 The retention rate of Zanthoxylum bungeanum essential oil in the film after air-drying and film formation of ZCZPE / CMC composite coating liquid with different ZCZPE addition ratios (relative to ZCZPE / CMC composite coating liquid) is shown. The results show that with the increase of ZCZPE addition ratio, the retention rate of Zanthoxylum bungeanum essential oil shows a trend of first decreasing and then increasing. The retention rate of Zanthoxylum bungeanum essential oil in the film changes under the comprehensive regulation of pH value, particle size and ζ-potential in the ZCZPE / CMC composite coating liquid system. When the ZCZPE addition ratio is small, the pH value of the ZCZPE / CMC composite coating liquid system is not conducive to the stability of ZCZPE, but the high steric hindrance provided by the high concentration of CMC coating matrix makes ZCZPE maintain basic stability, so the retention rate of Zanthoxylum bungeanum essential oil is high. When the ZCZPE addition ratio is further increased to 20%, the stability of the system has decreased significantly, but thanks to the low addition ratio of ZCZPE at this time. Therefore, although the retention rate of Zanthoxylum bungeanum essential oil in the film has decreased, it still maintains a high value. As the retention rate of ZCZPE further increased, the high proportion of unstable ZCZPE caused the retention rate of Zanthoxylum bungeanum essential oil in the film to further decrease. However, when the addition ratio of ZCZPE increased to 50%, the retention rate of Zanthoxylum bungeanum essential oil in the film increased, because the pH value of the ZCZPE / CMC composite coating liquid system was closer to the pH range where ZCZPE could maintain stability. (4) Determination of rheological properties of ZCZPE / CMC composite coating liquid The static and dynamic rheological properties of the emulsions prepared in the above examples and comparative examples were measured using a 40 mm aluminum Bohr plate fixture. The shear rate was adjusted to 0.01 to 100 s -1 , and recorded the apparent viscosity of the ZCZPE / CMC composite coating solution containing different ZCZPE addition ratios. When the strain was fixed at 0.1%, the angular frequency was adjusted from 0.1 to 100 rad / s, and the changes in the storage modulus (G') and loss modulus (G") of the emulsion were recorded. The storage modulus, loss modulus and loss tangent of the ZCZPE / CMC composite coating liquid prepared in the above examples and comparative examples were measured. from Figure 3 (A) It can be seen that with the increase of shear rate, the apparent viscosity of CMC and all composite coating liquids continues to decrease, showing obvious shear thinning behavior. At the same time, it can be found that with the increase of ZCZPE addition ratio, the apparent viscosity of the composite coating liquid is also decreasing, indicating that the addition of ZCZPE has destroyed the internal structure of the CMC coating matrix. The composite coating liquid is becoming thinner, but the composite coating liquid is still a pseudoplastic fluid. Figure 3 (C) and (D) show that with the increase of angular frequency, the G' and G" of the CMC coating matrix and all composite coating solutions continue to increase. With the increase of the addition ratio of ZCZPE, the G' and G" of the composite coating solution basically follow a decreasing trend, which also proves that the addition of ZCZPE destroys the internal network of the CMC coating matrix. Figure 3 (B) It was found that with the increase of angular frequency, the loss tangent angle continued to decrease and finally became less than 1, indicating that the internal structure of the ZCZPE / CMC composite coating liquid changed with the increase of angular frequency. (5) Evaluation of the antioxidant capacity of ZCZPE / CMC composite coating liquid The DPPH scavenging rate of the ZCZPE / CMC composite coating liquid prepared in the above examples and comparative examples was determined. The concentration of the DPPH methanol solution used was 100 μmol / L. 400 μL of the sample was mixed with 4 mL of the reaction solution, and the reaction was carried out at 25°C for 30 minutes. The absorbance value was measured at 517 nm, and light was protected throughout the process. The DPPH scavenging rate of the ZCZPE / CMC composite coating liquid prepared in the above examples and comparative examples was calculated according to the following formula: D=(A 0 -A 1 ) / A 0 ×100% Wherein, D(%) is DPPH clearance rate; A 0 is the absorbance value of the blank group; A 1 is the absorbance value of the experimental group. Determination of ABTS of the ZCZPE / CMC composite coating solution prepared in the above examples and comparative examples + · Clearance rate. Prepare 7mmol / L ABTS + Solution and 2.45mmol / LK 2 S 2 O 8 The two solutions were mixed and reacted at 25°C in the dark for 12 hours to obtain ABTS + Stock solution, ABTS + The working solution was obtained by diluting the stock solution until the absorbance at 734 nm was 0.700 ± 0.020. Deionized water was added as a blank control, and 100 μL of the sample was mixed with 6.0 mL of ABTS. + The diluted solutions were mixed, reacted at 30°C for 15 minutes, and then the absorbance was measured at 734 nm. The ABTS of the ZCZPE / CMC composite coating solution prepared in the above examples and comparative examples was calculated according to the following formula: + Clearance rate: A=(A 0 -A 1 ) / A 0 ×100% Where A(%) is the ABTS+ clearance rate; A 0 is the absorbance value of the blank group; A 1 is the absorbance value of the experimental group. from Figure 4 It can be seen that with the increase of ZCZPE addition ratio, the ZCZPE / CMC composite coating solution has a greater effect on DPPH free radicals and ABTS + The free radical scavenging ability is also increasing significantly, showing an obvious positive correlation. This is mainly because with the increase of the ZCZPE addition ratio, the content of pepper essential oil with strong free radical scavenging ability in the composite coating liquid system is also increasing. When the ZCZPE addition ratio is 50%, the prepared ZCZPE / CMC composite coating liquid has a strong free radical scavenging ability against DPPH free radicals and ABTS + The free radical scavenging rates were 47.38% and 49.24%, respectively, which were 15.7 times and 1.36 times higher than those of the coating with a ZCZPE addition ratio of 10%. This shows that DPPH free radicals are more sensitive to the increase in the ZCZPE addition ratio, that is, the change in the concentration of Zanthoxylum essential oil in the system. (6) Evaluation of antibacterial ability of ZCZPE / CMC composite coating liquid Determine the inhibition zone of the ZCZPE / CMC composite coating liquid prepared in the above examples and comparative examples. Take 200 μL of the Escherichia coli or Staphylococcus aureus dilution and evenly apply it on the LB agar plate. Place a 6 mm diameter sterile filter paper on the LB agar medium plate, and drop 20 μL of sample on each filter paper. After the plate is cultured at 37°C for 24 hours, observe the size of the inhibition zone and measure the diameter of the inhibition zone, and take the average of the three measurement results. The inhibition rate of the ZCZPE / CMC composite coating solution prepared in the above examples and comparative examples was detected by plate colony counting method. 2 mL of diluted bacterial solution was mixed with 30 μL of sample and cultured at 37°C for 2 hours with shaking. After diluting the obtained bacterial solution to a suitable concentration, 200 μL was evenly spread on the LB agar medium plate, and the plate was cultured at 37°C for 24 hours to count the colonies. The inhibition rate of the ZCZPE / CMC composite coating solution prepared in the above examples and comparative examples was calculated according to the following formula: I=(AB) / B×100 Wherein, I (%) is the inhibition rate; A is the number of colonies in the deionized water reference; and B is the number of colonies in the sample. The antibacterial zone can prove the antibacterial effect of the composite coating liquid, and the size of the antibacterial zone diameter is also a direct reflection of the antibacterial strength of the composite coating liquid. As shown in Table 1, the diameter of the antibacterial zone of the CMC coating matrix in the control group against Escherichia coli and Staphylococcus aureus is 0, indicating that CMC itself has no antibacterial activity. When ZCZPE is added, the diameter of the antibacterial zone of the composite coating liquid is significantly improved, and the diameters of the antibacterial zones for Escherichia coli and Staphylococcus aureus reach 8.5mm and 6.42mm respectively. The main substance that has an antibacterial effect is pepper essential oil. It can also be seen that the composite coating liquid has different inhibitory effects on the two pathogens, and the inhibition of Escherichia coli is stronger. With the continuous increase of the proportion of ZCZPE added in the composite coating liquid, the diameter of the inhibition zone of the composite coating liquid against the two pathogens is also increasing significantly. When the ZCZPE addition ratio is 50%, the diameter of the inhibition zone of the composite coating liquid against the two pathogens is also the largest, which is 11.77mm for Escherichia coli and 9.18mm for Staphylococcus aureus. In order to obtain more information on the antibacterial effect of the composite coating liquid, an inhibition rate experiment was further conducted. Table 1 Inhibition zone diameters of ZCZPE / CMC composite coating liquid against Escherichia coli and Staphylococcus aureus at different ZCZPE addition ratios Note: Different letters (af) indicate significant differences among different treatment groups (p<0.05) from Figure 5It can be seen that as the addition ratio of ZCZPE continues to increase, the inhibition rate of the composite coating liquid on Escherichia coli and Staphylococcus aureus is also increasing. It is worth noting that the inhibition rate of the composite coating liquid on Staphylococcus aureus continues to increase significantly with the increase in the addition ratio of ZCZPE (p<0.05), and finally reaches 90.8%. The increase in the inhibition rate of the composite coating liquid on Escherichia coli is no longer significant after the addition ratio of ZCZPE reaches 30%. The reason is that the composite coating liquid has a stronger inhibitory effect on Escherichia coli. When the addition ratio of ZCZPE reaches 30%, the inhibition rate of the composite coating liquid on Escherichia coli reaches 95.83%, which is consistent with the conclusion of the inhibition zone experiment. The strong antibacterial effect will also enable the composite coating liquid to achieve better preservation effect in practical applications. Application of the ZCZPE / CMC composite coating liquid of the present invention in preserving fresh red peppers: The ZCZPE / CMC composite coating liquid prepared in Example 3 was used for the preservation test: Select fresh red peppers with consistent color, maturity and no damage on the surface, wash the red peppers in deionized water for 2 minutes to wash away dust and impurities on the surface of the fruit. Then rinse with deionized water again and place it at room temperature to air dry for 1 hour to keep the fruit dry. Soak the fresh red peppers in the ZCZPE / CMC composite coating liquid for 1 minute, then take out the fresh red pepper fruits and air dry them. Put the fresh red pepper fruits in a polypropylene fresh-keeping box and seal them with polyethylene fresh-keeping film to maintain their relative humidity. Store the fresh-keeping box at 15-20℃ and 75% humidity, and test the physiological and biochemical indicators such as weight loss rate, decay index, chroma, hardness, soluble solids content, malondialdehyde content, polyphenol oxidase activity and peroxidase activity of the fresh red peppers on the 0th, 5th, 10th, 15th and 20th days, and use at least three peppers for each indicator. The blank group did not receive any treatment and was treated with sterile water. Soak the fresh red peppers in sterile water for 1 min, then take out the fresh red pepper fruits and air-dry them. The control group (CMC group) used CMC coating liquid The preparation method of CMC coating liquid comprises the following steps: taking 1.5g CMC, adding 100mL deionized water, stirring and dissolving in a constant temperature water bath to form a uniform and transparent film liquid; adding 0.75g glycerol and continuing stirring for 1h; Soak the fresh red pepper in the CMC coating solution for 1 min, then take out the fresh red pepper fruits and air-dry them. Performance Test: (1) Changes in weight loss rate of red pepper The weight of fresh red pepper fruits in each group was weighed on the 0th, 5th, 10th, 15th and 20th days, and the weight loss rate was calculated according to the following formula. Weight loss rate (%) = (W 0 -W n ) / W 0 Where W 0 (g) is the initial weight of fresh red pepper fruit, W n (g) is the weight of fresh red pepper fruit on day n. Figure 6 The figure shows the effects of different treatments on the weight loss rate of fresh red peppers on days 0, 5, 10, 15, and 20. As can be seen from the figure, with the extension of storage time, the weight loss rate of all components is increasing. This is caused by the loss of water by the transpiration and respiration of the fresh red peppers themselves. For the coating treatment group, the evaporation of water during storage also has a certain effect on the weight loss rate data. Since the 10th day, the weight loss rate of the composite coating group has been significantly lower than that of the blank control group, and the weight loss rate of the CMC coating group is lower than that of the blank coating group, but it has not reached a significant level. The reason may be that in addition to the inhibition of the loss of water by transpiration of new red peppers and fruits and vegetables by the coating structure, the essential oil of pepper contained in the composite coating group may also indirectly reduce the loss of water by affecting the physiological activities of fresh red pepper fruits. Therefore, the ZCZPE / CMC composite coating liquid can reduce the increase in the weight loss rate of fresh red peppers during storage and maintain the storage quality of fresh red peppers. (2) Changes in the decay index of red peppers Fresh red pepper fruits are divided into five decay grades according to the degree of decay on their surface. Each grade corresponds to a different decay score. The grading rules and scores are shown in Table 2. Table 2 Scoring criteria for fresh red pepper fruit decay According to the evaluation criteria in Table 2, fresh red pepper fruits were graded and the scores were recorded. The calculation formula of the decay index is as follows: Decay index = ∑ (number of fruits × fruit grade score) / (highest grade score × total number of fruits) Depend on Figure 7It can be seen that the decay index increases with the extension of storage time. The blank control group and the CMC group began to decay on the 5th day of storage, but in the subsequent storage, the decay of the fresh red peppers in the CMC group was lower than that in the blank control group. This shows that the dense structure covered by the coating on the surface of the fresh red pepper fruit effectively prevented the contamination of microorganisms and reduced the decay index. The ZCZPE / CMC composite coating liquid group did not decay in the early stage of storage, and only a small amount of decay occurred on the 15th day. During the subsequent storage period, the decay index remained low. The ZCZPE / CMC composite coating liquid group maintained the lowest decay index throughout the storage period. In addition to the influence of the dense structure formed by the composite coating liquid on the surface of the fruit, the pepper essential oil in the composite coating liquid also played an important role in inhibiting the bacterial flora that caused the corruption of fresh red peppers. (3) Color changes of red peppers The appearance of red peppers was photographed and recorded on the 0th, 5th, 10th, 15th and 20th days respectively, and the L*, a* and b* values ​​of the surface of each group of fresh red pepper fruits were measured and recorded using a colorimeter. Multiple points were selected on the surface of the fruit for testing, with the number of points not less than 3, and the total color difference ΔE was calculated using the following formula: Figure 8 The figure shows the changes in the appearance of the fresh red peppers in each treatment group during storage. As can be seen from the figure, on the 0th day, the surface color of the fresh red peppers was bright red, full in color, and high in brightness, indicating excellent quality. After 5 days of storage, the color of the fresh red peppers in the blank group and the CMC group became dim, the tail lost water significantly, and black spots appeared. On the 10th day, the overall color of the fruit gradually changed from bright red to dark red, and the longer the storage time, the more obvious the color change. At the same time, during the storage period, the color of the fresh red peppers in the ZCZPE / CMC composite coating liquid group was fuller and brighter than the other two groups, and the longer the storage time, the more obvious the difference. from Fig. 9 As shown in (A), during the entire storage process, the order of L* values ​​from high to low among the three treatments was ZCZPE / CMC>CMC>blank control group. The brightness reduction of the fresh red pepper in the ZCZPE / CMC composite coating liquid group was significantly smaller than that in the other two groups, so that its L* value was always maintained at a high level. from Fig. 9 (B) and (C) show that with the extension of storage time, the a* and b* values ​​of fresh red peppers continued to decrease. There was no significant difference between the CMC group and the blank control group, while the a* and b* values ​​of the ZCZPE / CMC composite coating liquid group were significantly higher than those of the other two groups, with the smallest change range. The ΔE value combines the changes in L* value, a* value and b* value. The ΔE value can be used to more specifically see the changes in the overall color of the surface of the bright red pepper. Fig. 9As shown in (D), with the extension of storage time, the ΔE value of fresh red peppers continued to rise, while the ΔE value of fresh red peppers in the ZCZPE / CMC composite coating liquid group remained at a low value, significantly lower than the other two groups. In summary, the ZCZPE / CMC composite coating liquid significantly reduced the color deterioration of fresh red peppers during storage and maintained their appearance quality. (4) Changes in the hardness of red peppers The hardness of each group of fresh red pepper fruits was measured and recorded using a texture analyzer on days 0, 5, 10, 15 and 20, and multiple points were selected on the fruit surface for testing, with the number of points not less than 3. from Fig.10 It can be seen that with the extension of storage time, the hardness of the fresh red pepper fruit continues to decrease. The hardness of the fresh red pepper fruit in the CMC group was significantly higher than that in the blank control group, which proves the effect of the coating on delaying the decline in the hardness of the fresh red pepper fruit. The reason is that the coating inhibits the respiration rate of the fresh red pepper fruit and delays the aging and corruption of the fruit. The pepper essential oil contained in the ZCZPE / CMC composite coating liquid not only has the effect of isolating the fruit from the outside world brought by the coating, but also can inhibit the aging of the fresh red pepper fruit. Fig.10 It also shows that the hardness of fresh red peppers in the ZCZPE / CMC composite coating liquid group was the highest in multiple measurements, and the hardness decline was the smallest among the three groups during the storage period, which played a significant effect in maintaining the hardness of fresh red pepper fruits and delaying their aging and corruption. (5) Changes in soluble solids content of red pepper At room temperature, the soluble solids content of fresh red pepper fruits in each group was measured using a handheld refractometer on days 0, 5, 10, 15 and 20. Depend on Fig.11 It can be seen that the change trend of the soluble solid content of fresh red peppers in each treatment group is first decreased and then increased. In the early stage, fresh red peppers consume carbohydrates for normal physiological metabolism, so the soluble solid content decreases. In the later stage of storage, the macromolecular substances in the fresh red pepper fruit are converted into soluble substances such as carbohydrates. During this period, the accumulation of soluble substances is greater than the consumption of physiological metabolism, so the soluble solid content increases. In addition, it can be found from the figure that whether in the early stage of the soluble solid content decrease or the later stage of the content increase, the change range of the soluble solid content in the fresh red pepper fruit of the ZCZPE / CMC composite coating liquid group is always smaller than that of the blank group, which shows that the composite coating liquid significantly inhibits the intensity of physiological metabolism of fresh red pepper fruits during post-harvest storage, delays its aging process, and improves its storage resistance. (6) Changes in MDA Content in Red Pepper The malondialdehyde (MDA) content of fresh red pepper samples was measured at 0, 5, 10, 15, and 20 days. First, the extract was prepared according to the experimental operation requirements and stored at 4°C. Then, the experimental data was obtained and the MDA content was calculated according to the requirements of the method. The final result was the MDA content per gram of fresh red pepper fruit. like Fig.12 As shown in the results, with the extension of storage time, the MDA content in the fruits of fresh red peppers in each group continued to accumulate and increase. In the first 10 days of storage, the MDA content in the fruits of fresh red peppers in the CMC group and the ZCZPE / CMC composite coating liquid group was significantly lower than that in the blank control group (p<0.05). After storage for 15 and 20 days, the MDA content in the fruits of fresh red peppers in the CMC group increased faster than that in the first 10 days. The MDA content in the fruits of fresh red peppers in the ZCZPE / CMC composite coating liquid group continued to increase, but the growth rate was lower than that of the other groups, and its MDA content was significantly lower than that of the other groups during the entire storage process (p<0.05). The change in MDA content proves that the coating inhibits the peroxidation of membrane lipids in fresh red pepper fruits and delays the aging and corruption process, and also proves that the addition of ZCZPE imparts functional properties to the CMC coating matrix and improves its preservation ability. The ZCZPE / CMC composite coating liquid group combined the inhibition of the physiological metabolism and membrane lipid peroxidation of fresh red pepper fruit by the coating and Zanthoxylum bungeanum essential oil, further delaying the senescence of the fruit. (7) Changes in polyphenol oxidase activity of red pepper The polyphenoloxidase (PPO) activity of fresh red pepper samples was measured at 0, 5, 10, 15, and 20 days. First, prepare the PPO enzyme extract according to the experimental operation requirements and store it at 4°C for later use. Then, obtain the experimental data and calculate the PPO activity according to the requirements of the method. The final result unit is ΔOD 420 / (min·g), where an increase of 1 in the absorbance change per minute for each gram of fresh red pepper fruit represents 1 activity unit. from Fig.13 It can be seen that with the extension of storage time, the PPO activity in the fresh red pepper fruits of each treatment group continued to increase. From the 5th day, the PPO activity of the ZCZPE / CMC composite coating liquid group, the CMC coating group and the blank control group showed significant differences. (p<0.05), during the entire storage process, the PPO activity of the ZCZPE / CMC composite coating liquid group was significantly lower than that of the other groups (p<0.05), and the PPO activity of the CMC coating group was significantly lower than that of the blank control group except on the 10th day, and at other test time points (p<0.05). The experimental results show that the ZCZPE / CMC composite coating liquid group has the best preservation effect on fresh red pepper fruit among the treatment groups, which can significantly inhibit the increase of PPO activity of fresh red pepper during storage, reduce the degree of browning, and extend the shelf life. (8) Changes in peroxidase activity of red pepper The peroxidase (POD) activity of fresh red pepper samples was measured at 0, 5, 10, 15, and 20 days. First, prepare the POD enzyme extract according to the experimental operation requirements and store it at 4°C for later use. Then, obtain the experimental data and calculate the POD activity according to the requirements of the method. The final result unit is ΔOD 470 / (min·g), where an increase of 1 in the absorbance change per gram of fresh red pepper per minute represents 1 activity unit. from Fig.14 It can be seen that the POD activity in the fresh red pepper fruit continued to increase during the storage period. During the entire storage period, the ranking of POD activity in each treatment group remained: blank control group > CMC coating group > ZCZPE / CMC composite coating liquid group, and the differences between the groups were significant (p<0.05). The same conclusion was drawn from the changes in PPO activity in fresh red pepper fruit. The ZCZPE / CMC composite coating liquid group significantly inhibited the increase in POD activity during storage and delayed the aging process of the fruit, and had the best preservation effect among all treatment groups. The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing an active coating liquid loaded with Zanthoxylum bungeanum essential oil, characterized in that: The preparation method is as follows: S1: Zein was completely dissolved in 85% ethanol, and the precipitate was removed by centrifugation to obtain a supernatant; the supernatant was added dropwise to distilled water under magnetic stirring, and concentrated by a rotary evaporator after ultrasonic treatment to obtain 3.5% zein nanoparticles; S2: Add citrus pectin to distilled water and stir overnight at 25°C until fully hydrated to obtain a 3.5% citrus pectin solution; S3: Using the electrostatic adsorption method, 3.5% zein nanoparticles were dropped into the citrus pectin solution under magnetic stirring to obtain zein-citrus pectin Pickering emulsion; S4: Zanthoxylum bungeanum essential oil and 3.5% zein-citrus pectin Pickering emulsion were mixed, and treated with a high-speed disperser at 14000 rpm for 4 min to obtain a Zanthoxylum bungeanum essential oil-loaded Pickering emulsion; S5: Take sodium carboxymethyl cellulose, add deionized water, stir and dissolve in a constant temperature water bath to form a uniform and transparent membrane solution; add glycerol and continue stirring for 1 hour; S6: Add 30-50% Pickering emulsion loaded with Zanthoxylum bungeanum essential oil at room temperature, stir magnetically at a speed of 800 rpm for 1 hour, and let stand to degas, so as to obtain an active coating liquid loaded with Zanthoxylum bungeanum essential oil.

2. The method for preparing an active coating liquid loaded with Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: In step S1, the centrifugal speed is 5000 g and the centrifugal time is 10 min.

3. The method for preparing a Zanthoxylum bungeanum essential oil-loaded active coating liquid according to claim 1, characterized in that: In step S1, the ultrasonic power is 600 W and the duration is 10 min.

4. The method for preparing an active coating liquid loaded with Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: In step S3, the volume ratio of 3.5% zein nanoparticles to 3.5% citrus pectin solution is 1:(2-4).

5. The method for preparing an active coating liquid loaded with Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: In the step S4, the volume ratio of Zanthoxylum bungeanum essential oil to 3.5% zein-citrus pectin Pickering emulsion is 1:(8-10).

6. The method for preparing an active coating liquid loaded with Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: The mass volume ratio of sodium carboxymethyl cellulose / deionized water and glycerol in step S5 is 6 g:400 mL:3 g.

7. Use of the active coating liquid loaded with Zanthoxylum essential oil prepared by the preparation method according to any one of claims 1 to 6 in preserving fresh red peppers.

Citation Information

Patent Citations

  • Clove essential oil Pickering emulsion coating preservative and preparation method and use thereof

    CN113712072A

  • Nano-emulsion for fresh keeping of meat products as well as preparation method and application of nano-emulsion

    CN115968932A

  • Preparation method of pepper leaf essential oil emulsion and application of pepper leaf essential oil emulsion in bacteriostasis, sterilization and pepper preservation

    CN118805823A

  • Sichuan pepper essential oil Pickering emulsion starch-based active composite membrane and preparation method thereof

    CN119081187A

  • Clove essential oil pickering emulsion-based coating preservative, and preparation method and use thereof

    US20230069246A1